2020
DOI: 10.3390/cryst10040279
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Plastic Behavior in an Extruded Long-Period Ordered Structure Mg90Y6.5Ni3.5 (at.%) Alloy

Abstract: The Mg 90 Y 6.5 Ni 3.5 alloy composed almost completely of the Long-Period-Stacking-Ordered (LPSO) phase has been prepared by casting and extrusion at high temperature. An elongated microstructure is obtained where the LPSO phase with 18R crystal structure is oriented with its basal plane parallel to the extrusion direction. Islands of α-magnesium are located between the LPSO grains. The mechanical properties of the alloy are highly anisotropic and depend on the stress sign as well as the relative orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Garces et al demonstrated that kinking of LPSO phases increases plastic deformation [12]. Zhang et al discovered that kinking of LPSO phases and DRX can coordinate the plastic deformation, and kinking of LPSO phases can delay the DRX at 350-450 • C [13].…”
Section: Introductionmentioning
confidence: 99%
“…Garces et al demonstrated that kinking of LPSO phases increases plastic deformation [12]. Zhang et al discovered that kinking of LPSO phases and DRX can coordinate the plastic deformation, and kinking of LPSO phases can delay the DRX at 350-450 • C [13].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of transition metals and rare-earth elements under favorable processing conditions leads to the formation of long-period stacking order (LPSO) structures, providing outstanding roomand elevated-temperature strength. Garcés et al [1] investigated the deformation behavior of an extruded Mg90Y6.5Ni3.5 alloy with an almost fully LPSO structure at different temperatures by means of in situ synchrotron radiation diffraction during compression. The results show an anisotropy in strength between the extrusion and the transversal direction.…”
mentioning
confidence: 99%